'Don't let the bastards grind you down': Feminist resilience/resilient feminism in The Handmaid's Tale (Hulu, 2017–). (September 2021) - Gorton, Kristyn
This article explores the tension that lies in the construction of resilience, which is at once, hopeful and inspiring and yet also in danger of positioning the individual as responsible for the lack of welfare and support that is available. In articulating these contradictory readings, I treat The Handmaid's Tale as a 'site where the meaning of feminism(s) is produced and contested' (Ferreday and Harris, 2017: 240) and as a television text whose storytelling techniques reflect what Jason Mittell (2015) refers to as 'narrative complexity'.